PENGARUH PRAKERIN DAN KONSEP DIRI TERHADAP RENCANA KARIR PESERTA DIDIK KELAS XII SMKS MANDIRI - Mardiana Safitri; Mashudi Mashudi; Achmadi Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
Prakerin is an activity that must be carried out by class XII students because to improve the competence of students in accordance with the needs of the world of work, it is necessary to learn outside formal and non-formal education units through fieldwork practices or commonly referred to as prakerin, in achieving a career plan only pre-employment is not enough to prepare students. Therefore, it is necessary to have self-concept from students to know their passion, character and desires. The method used in this study is quantative with the Ex Post Facto type of research. Based on the results of research and discussion in the first hypothesis, it shows that pre-employment has a significant effect on the student's career plan by 68,1% with the regression equation Y=17.915+ 0.821X1. The second hypothesis shows that self-concept has a significant effect on the student's career plan by 41,3% with the regression equation Y=30.938+0.194X2. The third hypothesis suggests that pre-employment and self-concept have a simultaneous significant effect on the learner's career plan by 70,4% with the regression equation Y=33,838+0,364X1+0,696X2. The second hypothesis shows that self-concept has a significant effect on the student's career plan by 41,3% with the regression equation Y=30,938+0,194X2. The third hypothesis suggests that pre-employment and self-concept have a simultaneous significant effect on the learner's career plan by 70,4% with the regression equation Y=33,838+0,364X1+0.696X2.